Synthesis and characterization of discotic liquid crystal molecule containing S-benzyldithiocarbazate - Mahmad Ayop, Fazilah; Silong, Sidik; Halim, Hafizah; Ab. Rahman, Mohamad Zaki; Wan Yunus, Wan Md. Zin; Abd. Moksin, Mohd Maarof (Universiti Putra Malaysia Press, 2005)
A liquid crystal molecule was successfully prepared by using S-benzyldithiocarbazate as precursor for the thio-mesogenic group and cyanuric acid derivative as the core reagent. The S-benzyldithiocarbazate intermediate was subjected to several steps of alkylation and condensation reactions to afford the pheriperal unit. The discotic liquid crystal was obtained with further reaction with 2,4,6-trichloro-[1,3,5]triazine. The precursor and the liquid crystal molecule have been characterized by elemental and spectroscopic methods. The phase-transition temperatures of the molecules were studied with differential scanning calorimetry, and the mesophase was identified with polarizing optical microscopy technique.